Image representative as an alternative reading technique for Dyslexic Children / Nik Nor Azidah Nik Aziz ... [et al.] - Nik Aziz, Nik Nor Azidah; Mohd Radzuan, Nurul Asyiqin; Abdullah, Khairul Zikri; Wan Zakaria, Wan Zamani (Universiti Teknologi MARA, Perak, 2020)
Dyslexic children who are said to have problems in learning actually have their unique learning styles. Thus, they required learning aids that are suitable with their conditions which are not similar with normal children. One of the issues of dyslexic children is the ability to figure out on how to peruse. Reading aptitudes are the most critical essential abilities. Without this ability, learning process is very challenging. Perceiving this significance and the motivation to support the dyslexic children, pondering or identification activity is led to distinguish the type of reading aids that are suitable to the necessities and requirements of dyslexic children. The case study was successfully conducted with children (6 to 9 years old) by Malaysian Dyslexia Association in Klang Valley, Malaysia. The finding from this preliminary research shows that reading in the form of interactive motion is easily accepted by the dyslexia children. In fact, the finding from this study provides a valuable learning style for these dyslexic children to use and practice. This new learning style is very enjoyable and manage to engage the children to read more in the classroom.